Integrated Omics Approaches to Explore a New System of Genetic Control of Dibenzothiophene Desulfurization and Aromatic Ring Cleavage by Gordonia alkanivorans Strain 135 - Ekaterina Frantsuzova; Alexander Bogun; Anna Vetrova; Elizaveta Kazakova; Tomiris Kusainova; Irina Tarasova; Irina Pozdnyakova-Filatova; Yanina Delegan (Biology)
Dibenzothiophene (DBT) is a widespread environmental pollutant. The most common metabolic pathway for DBT degradation by Gordonia strains is the 4S pathway, which is under the control of the dsz operon. The ability to utilize DBT as the sole source of sulfur in Gordonia alkanivorans strain 135 has been revealed. The dsz operon was not detected in the genome of strain 135. In this work, using genomic, transcriptomic, and proteomic data of strain 135, it was shown that an alternative pathway of DBT transformation is possible in non-dsz Gordonia; the sfnB and tauD genes and two acyl-dehydrogenase genes are significantly involved in the desulfurization process.